To simplify the expression \(-9\sqrt{140} - \sqrt{35}\), we start by simplifying the square roots.
-
Simplifying \(\sqrt{140}\): \[ \sqrt{140} = \sqrt{14 \times 10} = \sqrt{14 \times 2 \times 5} = \sqrt{2 \times 7 \times 2 \times 5} = \sqrt{4 \times 35} = \sqrt{4} \times \sqrt{35} = 2\sqrt{35} \] Therefore, \[ -9\sqrt{140} = -9 \times 2\sqrt{35} = -18\sqrt{35} \]
-
Now substituting back into the expression: \[ -18\sqrt{35} - \sqrt{35} \]
-
Combining like terms: \[ -18\sqrt{35} - 1\sqrt{35} = (-18 - 1)\sqrt{35} = -19\sqrt{35} \]
Thus, the final simplified form of the expression \(-9\sqrt{140} - \sqrt{35}\) is: \[ \boxed{-19\sqrt{35}} \]